2016
DOI: 10.1056/nejmoa1512711
|View full text |Cite
|
Sign up to set email alerts
|

Phase 3 Trials of Ixekizumab in Moderate-to-Severe Plaque Psoriasis

Abstract: In three phase 3 trials involving patients with psoriasis, ixekizumab was effective through 60 weeks of treatment. As with any treatment, the benefits need to be weighed against the risks of adverse events. The efficacy and safety of ixekizumab beyond 60 weeks of treatment are not yet known. (Funded by Eli Lilly; UNCOVER-1, UNCOVER-2, and UNCOVER-3 ClinicalTrials.gov numbers NCT01474512, NCT01597245, and NCT01646177, respectively.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

46
664
3
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 697 publications
(750 citation statements)
references
References 16 publications
46
664
3
10
Order By: Relevance
“…In all, 38 RCTs (identified in 38 reports)20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57 met the eligibility criteria and were included, as shown in Figure 1. These trials involved a total of 18 024 patients with plaque psoriasis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, 38 RCTs (identified in 38 reports)20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57 met the eligibility criteria and were included, as shown in Figure 1. These trials involved a total of 18 024 patients with plaque psoriasis.…”
Section: Resultsmentioning
confidence: 99%
“…Patients in 27 RCTs20, 21, 22, 25, 27, 28, 29, 30, 31, 34, 35, 36, 37, 38, 39, 40, 43, 45, 46, 47, 48, 50, 52, 53, 57 did not experience MACEs while exposed to any interventions but 10 MACEs were observed during the randomized controlled phase of nine studies 23, 26, 32, 33, 42, 44, 49, 51. Overall, the pooled analysis of these nine trials found that there was no statistically significant difference in the risk of MACEs when comparing biologic therapies with placebo (pooled OR 1·45, 95% CI 0·34–6·24, P  = 0·62), as shown in Figure 2a.…”
Section: Resultsmentioning
confidence: 99%
“…In light of data from other recent clinical trials, inhibition of IL‐17A does appear to have greater efficacy in terms of its impact on end points in patients with psoriasis 46, 47 and on PsA skin and joint disease end points 12, 13, as compared to its impact on joint disease end points in patients with RA 48, 49. These findings support immunohistologic observations of the importance of Th17 cells and IL‐17A in the pathogenesis of psoriasis 50, 51, 52.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent adverse events are nasopharyngitis, upper respiratory tract infection, injection-site reaction, injection-site erythema and headache [54].…”
Section: Secukinumabmentioning
confidence: 99%